Analisis Hubungan Faktor Internal Dan Eksternal Dengan Kinerja Bidan Desa Dalam Deteksi Dini Dan Penanganan Ibu Hamil Kekurangan Energi Kronik (KEK) di Kabupaten Grobogan Tahun 2015 - Rosmala Kurnia Dewi; Sri Achadi Nugraheni; Ayun Sriatmi (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2016)
Chronic Energy Deficiency (CED) is one of the causes of maternal and infant mortality indirectly. Maternal Mortality Rate (MMR) in Grobogan District increased gradually during the period of 2011 – 2012 from 26 cases (114.03/100,000 live births) to 34 cases (151.15/100,000 live births), and decreased sharply to be 22 cases (102.03/100,000 live births) in 2013. Meanwhile, Infant Mortality Rate (IMR) was 194 cases in 2011, rose dramatically in 2012 to be 240 cases, and declined sharply in 2013 to be 166 cases. Low Birthweight Babies (LBWB) was one of the causes of infant mortality because pregnant women suffered from CED during their pregnancies. The aim of this study was to analyse internal and external factors with performance of village midwives in conducting early detection and handling pregnant women with CED. This was an observational-analytic study using cross-sectional approach. Data were collected using structured questionnaires. Population was 243 village midwives at health centres in Grobogan District. As many as 71 village midwives were selected randomly using a technique of stratified random sampling. Data were analysed using analyses of bivariate (chi square test) and multivariate (logistic regression test). The results of this research showed that most of the respondents aged ranging from 20-35 years old (76.1%), had working period less than or equal to 6 years (53.5%), ever handled CED (81.7%). Variables of health facilities (p=0.001), fellow worker support (p=0.016), community support (p=0.001), leader support (p=0.0001) had significant relationship with the performance of village midwives in conducting early detection of pregnant women with CED. Factors jointly influencing the performance were health facilities (p=0.000; Exp(B)=25.395), and leader support (p=0.001; Exp(B)=10.278). As suggestions, health centres and District Health Office need to provide complete health facilities to improve performance of health workers in providing services.